Infografis sebagai Media Informasi Mengenai Situs Sejarah di Desa Cisaat, Kecamatan Ciater, Kabupaten Subang, Provinsi Jawa Barat - Hadi Santosa, Firdaus; Umasih, Umasih; Hasan, Rinie Octaviany; Kadar, Raka El-Chuza Adnan; Christiono, Marchel (Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2023)
The purpose of this community service activity is to increase understanding and ability to make infographic media as information media about historical sites in Cisaat Village, Subang, West Java. This is because the use of infographic media is needed in delivering information about historical sites as a form of utilizing information technology and updating information dissemination. The partner in this activity is the Tourism Awareness Group of Cisaat Village, Ciater District, Subang Regency. Participants in this activity are the community, especially members of the tourism awareness group and youth who will become developers and preservers of historical sites. The method that will be used to be able to increase understanding and ability to make infographic media is to use seminars or workshops to members of the tourism awareness group and youth of the Cisaat village community. Through this activity, the output of community service activities is expected to be able to obtain (1) Intellectual Property Rights (IPR), (2) Publication of activity videos on YouTube, (3) Partner Certificate regarding an increase in partner empowerment according to the problem. (4) Online mass media publication.